2019
DOI: 10.3390/ijms20122918
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-Loaded Mesoporous Silica Nanoparticles Markedly Enhanced Cytotoxicity in Hepatocellular Carcinoma Cells

Abstract: Curcumin, a natural polyphenol extracted from a perennial herb Curcuma longa has been verified for many physiological activities such as anti-oxidant, anti-inflammatory, and anti-tumor properties. The direct use of curcumin cytotoxicity studies are limited due to its unstable chemical structure, low bioavailability, easy oxidation, and degradation by ultraviolet (UV) light etc. Trying to overcome this problem, silica-encapsulated curcumin nanoparticles (SCNP) and chitosan with silica co-encapsulated curcumin n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 88 publications
4
35
0
Order By: Relevance
“…In the present study, data obtained from the xenograft nude mouse model provided further evidence that curcumin effectively suppressed the growth of liver cancer. Similarly, numerous previous in vitro and in vivo studies have demonstrated that curcumin inhibits the growth cancer in both animals and humans ( 40 42 ), including hepatocellular carcinoma ( 43 ). Several reports have suggested that curcumin or its derivative alone or in combination with other drugs exhibit favorable anti-liver cancer activity ( 44 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, data obtained from the xenograft nude mouse model provided further evidence that curcumin effectively suppressed the growth of liver cancer. Similarly, numerous previous in vitro and in vivo studies have demonstrated that curcumin inhibits the growth cancer in both animals and humans ( 40 42 ), including hepatocellular carcinoma ( 43 ). Several reports have suggested that curcumin or its derivative alone or in combination with other drugs exhibit favorable anti-liver cancer activity ( 44 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, it forms a complex with ferric chloride, which shows absorbance at 700 nm [34]. Next, chelating activities of antioxidants were evaluated by inhibition in the formation of Fe 2+ -ferrozine complex, which has an absorbance at 562 nm [35]. EDTA was used as a positive control in this assay.…”
Section: In Vitro Antioxidant Activities Of Polysaccharidesmentioning
confidence: 99%
“…The ferrous ion chelating activity was measured by following the previously described method with a slight modification [35]. Briefly, 0.1 mL polysaccharide sample was added to 0.5 mL ferrous chloride (0.2 mM) and 0.2 mL ferrozine (5 mM), followed by incubation at room temperature for 10 min.…”
Section: Ferrous Ion Chelating Activitymentioning
confidence: 99%
“…47 Silica NPs were chosen as a nanoplatform given their low toxicity to both prokaryotes 48 and eukaryotes 49 and low environmental impact. 50 Despite the fact that, for silica NPs, curcumin is oen delivered in mesoporous silica [51][52][53] or added to the silica matrix itself, 54 here the compound is functionalised covalently only at the surface of the NPs. The NPs produced are shown to have little antibacterial effect, however a noticeable antibiolm activity.…”
Section: Introductionmentioning
confidence: 99%